Methods of Determining Amortization Periods for Non-Conforming Uses - Margaret Collins (Washington University Journal of Law & Policy, 2000)
In the mid-1990s the Planning Department of the Hong Kong government became interested in the American concept of the amortization of non-conforming uses to eliminate noxious land uses threatening the viability of residential areas. Dan Mandelker, my former law professor, led a panel of international experts. The panel served as advisors to the Hong Kong planners on the American experience with amortization and to help them establish a well-conceived, comprehensive, and legally-defensible approach to establishing an amortization system in Hong Kong. Dan provided the historical and legal perspectives, while my own research focussed on techniques to determine amortization schedules for phasing out non-conforming uses. This Essay provides a brief summary of Professor Mandelker’s work and then discusses nuts-and-bolts approaches to (1) determining the costs to be amortized and (2) setting the amortization period to recover those costs.
Keywords: Amortization; Land use; Regulatory taking (Law)